Relationship between types of smartphone use among adolescents and smartphone addiction: focusing on gender differences - Sunghwan Cho; Seoyoon Lee; Hyun-Jae Woo; Yun-Hee Ko; Kyu-Hyoung Jeong (Journal of Men's Health)
Background: With the increasing prevalence of smartphone ownership among adolescents in South Korea, understanding usage patterns and their consequences has become a priority. This study aimed to examine smartphone usage patterns and their association with smartphone addiction, with a specific focus on gender differences. Methods: Data were derived from the 2022 Korean Children and Youth Panel Survey (KCYPS), which included 4524 adolescents. Latent profile analysis was used to identify distinct smartphone usage patterns based on the frequency of use across various activities. Multiple regression analysis was performed to assess the relationship between these usage patterns and smartphone addiction levels. Results: Four distinct smartphone usage profiles were identified for both genders. For males, these profiles included the “High Usage Group”, “Family & Friends Focused-Group”, “Moderate Usage Group” and “Family & Friends Focused-Low Usage Group”. Both male and female adolescents were predominantly categorized in the “Moderate” and “High Usage Groups”. Among males, those in the “High Usage Group” exhibited significantly higher levels of smartphone addiction compared to those in the “Family & Friends Focused-Group” and “Family & Friends Focused-Low Usage Group”, potentially due to excessive use of social networking, gaming and video-watching applications. Female adolescents in the “High Usage Group” demonstrated higher addiction levels compared to the “Family & Friends Focused-Group” and “Moderate Usage Group”, which may be associated with reduced engagement in intimate peer relationships and emotional sharing in groups with less frequent smartphone use. Conclusions: These findings indicate the necessity for gender-specific interventions to address smartphone addiction among adolescents, emphasizing the importance of developing targeted strategies for addiction prevention and policy formulation.